2020
DOI: 10.1371/journal.pone.0234917
|View full text |Cite
|
Sign up to set email alerts
|

Self-reports of Dutch dog owners on received professional advice, their opinions on castration and behavioural reasons for castrating male dogs

Abstract: Male dogs are often castrated based on the thought that it facilitates well-behavedness. However, the causal evidence for this from prospective studies lacks and the existing associative studies present mixed results depending on the studied behaviours. We aimed to gain insight into possible factors driving an owner's decision to castrate their male dog, through a quantitative survey based on a convenience sample. We determined the advice owners received from three types of dog professionals (veterinarian prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
2
4
0
5
Order By: Relevance
“…A survey in the UK found that citizens were predominantly supportive of dog and cat neutering [ 76 ]. Dog owners in The Netherlands said that correcting unwanted behaviors was an important reason to have their male dogs neutered [ 77 ], supporting that perception of necessity may lead to support of the practice. In another study, Spanish consumers that were not aware that pigs are castrated said that it would not be a welfare issue if pigs were castrated in the same way domestic pets [ 78 ], something that was also suggested by some participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A survey in the UK found that citizens were predominantly supportive of dog and cat neutering [ 76 ]. Dog owners in The Netherlands said that correcting unwanted behaviors was an important reason to have their male dogs neutered [ 77 ], supporting that perception of necessity may lead to support of the practice. In another study, Spanish consumers that were not aware that pigs are castrated said that it would not be a welfare issue if pigs were castrated in the same way domestic pets [ 78 ], something that was also suggested by some participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…De onderliggende redenen waarom eigenaars ervoor kiezen gonadectomie bij hun hond electief te laten uitvoeren, zijn voor de hand liggend: het steriel maken van de reu of teef, het vermijden van de ongemakken gerelateerd aan loopsheid en het vermijden van aandoeningen van het genitale stelsel. Wat de reu betreft, meldt 58% van de eigenaars dat het corrigeren of vermijden van ongewenst gedrag een reden is om hun hond te laten castreren (Roulaux et al, 2020). De keuze voor gonadectomie wordt mede bepaald door factoren, zoals de culturele achtergrond, de wetgeving van een bepaald land, de economische status van de eigenaar, het geslacht van de eigenaar en de relatie tussen eigenaar en hond (Downes et al, 2015).…”
Section: Inleidingunclassified
“…De keuze voor gonadectomie wordt mede bepaald door factoren, zoals de culturele achtergrond, de wetgeving van een bepaald land, de economische status van de eigenaar, het geslacht van de eigenaar en de relatie tussen eigenaar en hond (Downes et al, 2015). In het beslissingsproces van de eigenaar voor electieve gonadectomie speelt het advies van de dierenarts een belangrijke rol (Roulaux et al, 2020). In landen zoals het Verenigd Koninkrijk en in mindere mate ook België wordt gonadectomie door veel dierenartsen aangeraden bij niet-fokdieren in het kader van de gezondheid van het dier en het gemak voor de eigenaar.…”
Section: Inleidingunclassified
See 2 more Smart Citations